Combined Oral and Topical Application of Pumpkin (Cucurbita pepo L.) Alleviates Contact Dermatitis Associated With Depression Through Downregulation Pro-Inflammatory Cytokines - Balgoon, Maha Jameal; Al-Zahrani, Maryam H.; Jaouni, Soad Al; Ayuob, Nasra (Frontiers in Pharmacology, 2021)
Background: Depression and contact dermatitis (CD) are considered relatively common health problems that are lined with psychological stress. Antioxidant, anti-inflammatory, antidepressant activities of pumpkin were previously reported. Objectives: This study aimed to evaluate the efficacy of the combined topical and oral application of pumpkin fruit (Cucurbita pepo L.) extract (PE) on relieving CD associated with chronic stress-induced depression compared to the topical pumpkin extract alone and with the standard treatment. Materials and methods: Forty male albino rats were exposed to chronic unpredictable mild stress (CUMS) for 4 weeks for induction of depression then exposed to (1-fluoro-2, 4-dinitrofluorobenzene, DNFB) for 2 weeks for induction of CD. The rats were then divided into 4 groups (n=10 each); the positive control, Betaderm-treated, PE-treated and PE cream and oral-treated groups. Depression was behaviorally and biochemically confirmed. Pro-inflammatory cytokines TNF-α, IL-6, COX-2 and iNOS were assessed in the serum, skin and their mRNA levels were assessed using qRT-PCR. Oxidant/antioxidant profile was assessed in the serum and skin. Histopathological and immunohistochemical assessment of skin samples was also performed. Results: Pumpkin extract, used in this study, included large amount of Oleic acid (about 56%). The combined topical and oral administration of PE significantly reduced inflammation and oxidative changes induced by CD associated with depression compared to the standard treatment of CD (Betaderm) and the topical PE alone. PE significantly alleviated signs and histopathological score of CD (p<0.001) through the significant down-regulation of pro-inflammatory cytokines and the significant up-regulation of antioxidants in the skin and serum. Significant down-regulation (p<0.001) of TNF-α, IL-6, COX-2 and iNOS gene expression in PE-treated group confirmed the anti-inflammatory action of PE. Conclusion: Pumpkin extract, applied topically and orally, could be an alternative as well as preventive approach in treating contact dermatitis associated with depressive like behavior. Further studies to this effect on volunteer patients of contact dermatitis are recommended.